Enabling initiation of a lean management system in SMEs: a case study of a high performance plastics manufacturer - Jalali-Roudsari, Mehdi; Murray, Susan (Cranfield University Press, 2013)
This paper investigates the challenges in developing a Lean Management System in a typical Small to Medium Size Enterprise (SME’s) in the UK. Through a series of pilot projects measured and implemented by action research this case study reflects on the changes in mind-set and behaviours that are required on the part of the researcher in order to implement a Lean Manufacturing System. The implementation and suggestions by the researcher to adopt the observational methods such as visual data management and Hoshin Kanri were part of the action research. The data gathered influenced management strategy and planning to incorporate lean practices in the organisation. The actions and results were achieved by the workforce commitment to ensure embedding and sustainability for the future. Benefits realised included a 21% increase in on time delivery performance and cross functional problem solving actions resulted in a lead time reduction of 8 to 4 weeks.
Keywords: Lean Management System; Performance Management; Hoshin Kanri